2012
DOI: 10.4236/jeas.2012.23004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Speed of Pultrusion for Large-Sized Composite Rods

Abstract: The paper describes a mathematical model of the stress-strain state of polymer composite materials in the pultrusion process of large-sized products. The influence of the pull speed on the stress-strain state of the products is investigated. To determine the maximum possible pull speed series of solutions at different pull speeds are obtained. Depending on the maximum strain in the cross section of the rod determined the optimal value of pulling speed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The products are pulled from the dice rather than forced out by the pressure. A large number of profiles such as rod, tube, different types of structure can be produced by the pultrusion process [49,50,84].…”
Section: Compression Moldingmentioning
confidence: 99%
“…The products are pulled from the dice rather than forced out by the pressure. A large number of profiles such as rod, tube, different types of structure can be produced by the pultrusion process [49,50,84].…”
Section: Compression Moldingmentioning
confidence: 99%
“…, the value of tensile strength is optimal at the speed of 0.3 m/min. The decrease in tensile strength was reported by Krasnovskii and Kazakov that at high pulling speed of the pultruded composites, the strain occurred at the polymerized part of the pultruded composites may exceed the maximum allowable value. The phenomenon leads to poor matrix crosslinking and inadequate adhesion between fiber and matrix.…”
Section: Resultsmentioning
confidence: 87%
“…Krasnovskii and Kazakov reported in the thermoset pultrusion process, it is important to set the proper fiber pulling speed during pultrusion process. The pulling speed depends on the type of polymer matrix used, the amount of hardener and promoter used, and the size of the pultruded profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The approach is based on the hypothesis that at the border line temperature is constant. Analysis of the solution of heat conduction and polymerization by method of finite differences [8] showed that this hypothesis holds. The influence of the pull speed, the type of filler and fiber volume fraction on the position of the border polymerization line is investigated.…”
Section: Resultsmentioning
confidence: 99%